The effect of hydrocolloids on the stability and viscosity of cloudy apple juices - Genovese, Diego Bautista (2001)
The influence of xanthan gum (XG) and carboxymethylcellulose (CMC) on the colloidal stability of cloudy apple juice has been studied. Concentrations from 0.4-0.5% completely inhibited juice clarification. At lower gum concentrations, juices with CMC were more stable. Z-potential (ζ) was measured by laser doppler electrophoresis. As expected, cloudiness in apple juice increased its stability with |ζ| (the more electro-negative, the more stable) following a behavior common to both food gums. Therefore, stability of cloudy juices with food gums could be predicted only in terms of ζ. Log-log plot of apparent viscosity (ηa) vs (γ̇), showed a typical shear thinning behavior, with a transition from dilute to concentrated solution at some critical concentration. At low shear rates, XG was more viscous than CMC, demonstrating that the greater stabilizing effect of CMC was basically due to its electro-negativity. © 2001 Elsevier Science Ltd.